Influence of PapMV nanoparticles on the kinetics of the antibody response to flu vaccine. Issue 1 (December 2016) - Rioux, Gervais; Carignan, Damien; Russell, Alexis; Bolduc, Marilène; Gagné, Marie-Ève; Savard, Pierre; Leclerc, Denis
Abstract Background The addition of an adjuvant to a vaccine is a promising approach to increasing strength and immunogenicity towards antigens. Despite the fact that adjuvants have been used in vaccines for decades, their mechanisms of action and their influence on the kinetics of the immune response are still not very well understood. The use of papaya mosaic virus (PapMV) nanoparticles-a novel TLR7 agonist-was recently shown to improve and broaden the immune response directed to trivalent inactivated flu vaccine (TIV) in mice and ferrets. Results We investigated the capacity of PapMV nanoparticles to increase the speed of the immune response toward TIV. PapMV nanoparticles induced a faster and stronger humoral response to TIV that was measured as early as 5 days post-immunization. The addition of PapMV nanoparticles was shown to speed up the differentiation of B-cells into early plasma cells, and increased the growth of germinal centers in a CD4+ dependent manner. TIV vaccination with PapMV nanoparticles as an adjuvant protected mice against a lethal infection as early as 10 days post-immunization. Conclusion In conclusion, PapMV nanoparticles are able to accelerate a broad humoral response to TIV. This property is of the utmost importance in the field of vaccination, especially in the case of pandemics, where populations need to be protected as soon as possible after vaccination.